The Rise of Private Education in Northwest Syria - Beaujouan, Juline (My University, 2023)
This policy brief highlights how (I)NGOs and local communities favour investment in public schools to bridge the educational gap in northwest Syria. Recommendations for funding prioritization: Support the development of public schools, including access to and quality of public education, rather than investing in the private sector. Advocate for the empowerment of teaching staff and directorates, (I)NGOs and local communities on educational issues. Support accelerated learning programmes and remedial educational classes, to facilitate the re-insertion of drop-out students into the educational system. Encourage the development of online education for accessibility and inclusion, including training for teachers in delivering education through online platforms. Facilitate the inclusion of child protection measures in educational activities.
Keywords: Concepts; Syria